Establishing injury surveillance in emergency departments in Nepal: protocol for mixed methods prospective study (Global Health Research, 2025)
This article consists of a citation of a published article describing research funded by the Global Health Research programme under project number 16/137/49, and is provided as as part of the complete record of research outputs for this project. The original publication is available at: https://doi.org/10.1186/s12913-020-05280-9 Background Globally, injuries cause more than 5 million deaths annually, a similar number to those from HIV, Tuberculosis and Malaria combined. In people aged between 5 and 44 years of age trauma is the leading cause of death and disability and the burden is highest in low- and middle-income countries (LMICs). Like other LMICs, injuries represent a significant burden in Nepal and data suggest that the number is increasing with high morbidity and mortality. In the last 20 years there have been significant improvements in injury outcomes in high income countries as a result of organised systems for collecting injury data and using this surveillance to inform developments in policy and practice. Meanwhile, in most LMICs, including Nepal, systems for routinely collecting injury data are limited and the establishment of injury surveillance systems and trauma registries have been proposed as ways to improve data quality and availability. Methods This study will implement an injury surveillance system for use in emergency departments in Nepal to collect data on patients presenting with injuries. The surveillance system will be introduced in two hospitals and data collection will take place 24 h a day over a 12-month period using trained data collectors. Prospective data collection will enable the description of the epidemiology of hospital injury presentations and associated risk factors. Qualitative interviews with stakeholders will inform understanding of the perceived benefits of the data and the barriers and facilitators to embedding a sustainable hospital-based injury surveillance system into routine practice. Discussion The effective use of injury surveillance data in Nepal could support the reduction in morbidity and mortality from adult and childhood injury through improved prevention, care and policy development, as well as providing evidence to inform health resource allocation. This study seeks to test a model of injury surveillance based in emergency departments and explore factors that have the potential to influence extension to additional settings. Funding This publication was funded by the Global Health Research programme as a part of award number 16/137/49. This article reports on one component of the research award NIHR Global Health Research Group on Nepal Injury Research, University of the West of England, Bristol. For more information about this research please view the award page [https://fundingawards.nihr.ac.uk/award/16/137/49] DOI https://doi.org/10.1186/s12913-020-05280-9